Nature and Origin of Mineralizing Fluids in Hyperextensional Systems: The Case of Cretaceous Mg Metasomatism in the Pyrenees. (17th July 2019) - Quesnel, Benoît; Boiron, Marie-Christine; Cathelineau, Michel; Truche, Laurent; Rigaudier, Thomas; Bardoux, Gérard; Agrinier, Pierre; de Saint Blanquat, Michel; Masini, Emmanuel; Gaucher, Eric C.
Abstract : During the Albian, the hyperextension of the Pyrenean passive margin led to a hyperthinning of the continental crust and the subsequent subcontinental mantle exhumation. The giant Trimouns talc-chlorite deposit represents the most prominent occurrence of Albian metasomatism in the Pyrenees, with the occurrence of the largest talc deposit worldwide. Consequently, this deposit, which is located on a fault zone and a lithological contact, represents one of the major drains at the scale of the Pyrenees and one of the best geological targets in order to determine the origin(s) of the fluid(s) that circulated during this period. Talc-chlorite ore is characterized by the presence of brines trapped in dolomite, quartz, and calcite fluid inclusions in the vicinity of the talc-rich zone. Considered as being responsible for the formation of talc, these fluids may be interpreted in several ways: (i) primary brines expelled from Triassic evaporites, (ii) secondary brines produced through halite leaching by diagenetic/metamorphic fluids, and (iii) brines derived from seawater serpentinization of mantle rocks. Stable isotope analyses ( δ 13 C, δ 18 O, δ D, and δ 37 Cl) and Cl/Br ratio measurements in fluid inclusions and their host minerals were carried out in order to determine the origin of the fluid(s) involved in the formation of the ore deposit. The data are consistent with a primary brine origin for the mineralizing fluid, which could have been expelled from the Triassic levels. Other hypotheses have been tested, for example, the production of brines via the seawater concentration during serpentinization. The geochemical proxies used in this study provide equivocal results. The first hypothesis is by far the most realistic one considering the numerous occurrences of Trias formations nearby, their deformation during the extension, and the drainage of the expulsed brines as evidenced by the high-salinity fluid inclusions found all around the deposit. Alternatively, the exhumation of the mantle is considered as a major source of heat and stress that favored brine migration along the major shear zones. Our results fit well with brine circulation in a hyperextensional geodynamic context, which is related to the formation of the talc-chlorite ore, the thinning of the continental crust, and the exhumation of the subcontinental mantle, in accordance with recent works.